Empowerment of PKK in Keliling Benteng Ulu Village, West Martapura District by Utilizing TOGA into an Instant Drink with Commercial Value - Isnaini; Asnawati; Azma Rosida; Emmi Erliyanti; Nabilla Azzahra Ariady; Dinda Rohama; Jeniar Atmadela; Zahra Aprillita (PT FORMOSA CENDEKIA GLOBAL, 2023)
Keliling Benteng Ulu Village (KBU) in West Martapura Subdistrict, Banjar Regency, South Kalimantan, is an adopted village under the supervision of the Undergraduate Medical Study Program, Faculty of Medicine, Lambung Mangkurat University. Previously, they distributed TOGA plant seeds and conducted educational sessions on their benefits. In the current phase, five residents are selected for training in creating instant herbal drinks from TOGA plants, supported with necessary tools. The resulting herbal drink, named